An overview of the PAHTAT toolbox. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Pilleri, P.; Joblin, C.; Berné, O.; Montillaud, J.; Okada, Y.
Abstract: In this contribution, we briefly describe how an observed mid-infrared (5.5-14 μm) spectrum can be used to trace key physical conditions along a given line of sight, such as the UV radiation field, the ionization parameter and the dust column density. These parameters are often difficult to determine independently from PDR models. The PAHTAT toolbox offers the opportunity to analyze mid-IR spectra using a limited number of parameters, that are associated with the physical properties of the dust and gas being observed.